Rationalities, beliefs and pedagogical practices in the implementation of the school curriculum - Condori Gutiérrez, Juan Luis (2019)
This article proposes to develop a reflection about the type of rationality presents in the implementation of the school curriculum, and in its relationships with beliefs and pedagogical practice of the teacher. Let us consider that the dominant rationality in the curriculum is associated with technical interest that gives priority to the achievement of a product in relation to pre-established objectives, which are the learning standards. Furthermore, in the pedagogical practices underlie lag of beliefs related to the compliance of regulations reinforcing the idea that the curriculum should be developed in a rigid way, minimizing the practices of curricular construction from the experience of the teacher. Finally, the high prescriptive level established from its guidelines for its implementation presents a series of elements that constitute it as a prescription rather than as a relevant tool with the school.